Reproductive biology of Pristolepis grootii from the Lubuk Siam Oxbow Lake, Siak Hulu Sub-District, Kampar Regency, Riau Province - Asshabri, Fadli; Putra, Ridwan Manda; Windarti, Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPristolepis grootiiis type of fish commonly inhabit the Lubuk Siam lakes. However, information on reproductive biology of the fish is rare. To understand the biological aspects of this fish, a study was conducted from July to September 2019. The fish was sampled once / 2 weeks, 4 times. Parameters measured were sex ratio, gonad maturity level, gonad somatic index (GSI), fecundity and egg diameter.Result shown that there was 46 males and 59 females (sex ratio 1:1.3). The gonad maturity levelofmales and females during the research were various,  1st to 4th.  The gonad somatic index (GSI) of male was0.88% - 1.70%and that of the female was1.73% -5.37%. The average fecundity of the femaleswas 332,308-542,500 eggs/ fish. Egg diameter   was ranged from 0.48 to 0.63 mm and those eggs distribute evenly in the ovary and indicates that the fishis a whole spawner fish.Keword:sex ratio, gonad maturity level, gonad somatic index (GSI), fecundity, whole spawner.